Profile of Deaf Students at Batubara Special School with Achievements in National Pantomime Field - Edy Junianto; Marlina Marlina (Edumaspul: Jurnal Pendidikan, 2022)
The research was motivated by the findings of a deaf student at SLB Negeri Batubara who achieved achievements in pantomime art. Students' skills in performing pantomime movements are a long process until they can achieve achievements at the national level. This study aims to reveal what factors influence students to be able to achieve achievement, the obstacles faced and the solutions made to overcome them. The research method uses a case study with a qualitative approach. Sources of data consisted of outstanding deaf students, teacher trainers, parents and the head of the SLB Negeri Batubara. Collecting data using interview, observation, and documentation techniques. Data collection tools using interview guidelines, observation and document checklists. Data analysis using qualitative data analysis techniques Miles and Huberman. The results of the research obtained are achievements in the pantomime field from 2019 to 2021 at the Provincial and National levels. Internal factors that support students to excel come from interest in practicing and good physical condition. Meanwhile, external factors are supported by various parties, starting from teacher trainers, schools and parents. There are no significant obstacles faced by Mutia in achieving achievements. Mutia undergoes a training process and diligently participates in every competition. Keywords: deaf, pantomime, achievement, extracurricular